Adopsi Teknologi Informasi Dan Komunikasi Untuk Meningkatkan Kinerja Keuangan Umkm Berbasis Pangan Olahan Di Provinsi Lampung: Adopsi Teknologi Informasi Dan Komunikasi Untuk Meningkatkan Kinerja Keuangan Umkm Berbasis Pangan Olahan Di Provinsi Lampung - Sutarni sutarni (Politeknik Negeri Lampung., 2023)
The objectives of this study are (1) analyzing the types and utilization of ICT, (2) analyzing business profits and the effect of ICT adoption on MSME revenue performance, and (3) analyzing factors affecting the ICT adoption of processed food MSMEs in Lampung Province. This research was conducted in Lampung Province, covering Bandar Lampung City, Central Lampung Regency, Pringsewu Regency, South Lampung Regency, Metro City, and Pesawaran Regency. Locasi is determined intentionally (purposive), considering that the location has adequate ICT facilities and access. The samples from this research were MSME actors in the production of superior processed foods, especially banana chips, cassava chips, emping melinjo, tempe chips, eyek-eyek, crackers, jackfruit chips, and kelanting based on the KJPU in Lampung Province. This study used a sample of 40 respondents. This research is a survey method. The data used in this study were divided into two, namely primary data and secondary data. The research data were analyzed descriptively qualitatively and quantitatively. The data are tabulated, mathematically analyzed, and statistically analyzed according to the purpose of the study. The results showed that the highest level of ICT use used by processed food MSMEs in Lampung Province, namely mobile phones, reached 95%. The most widely used social media whatsapp reached 77.5%. The most widely used use of the marketplace is the shoppe marketplace, but the use of the marketplace as a marketing medium for processed food MSME products is relatively low, only reaching 30%. Internet usage is quite high, reaching 82.5% and respondents think that the internet has an important role in marketing products, communicating with customers, and finding packaging information and product labels. Adopsi of ICT by processed food MSMEs in Lampung Province is still relatively low. Business revenues for processed food MSME actors were obtained by IDR 4,213,737.50, business profits obtained by IDR 2,448,951.73 in 2021. The level of ICT use has a significant influence on the performance of Processed Food MSMEs.